Comparative evaluation of the accuracy of three different three-dimensional facial scanning systems: An observational crossover study - Lakshay Kumar; Subhabrata Maiti (The Journal of Indian Prosthodontic Society)
Aim: Facial imaging technology has become a pivotal tool in modern medical practice, particularly within fields such as maxillofacial prosthodontics, orthodontics, and smile design. The creation of digital twins, or virtual patients, enhances diagnostic accuracy, aids in treatment planning, and improves outcome prediction. The aim of the study was to assess the accuracy of various facial scanners, determine overall accuracy of each scanner, and identify which scanner demonstrates superior accuracy in specific facial regions. Settings and Design: An observational crossover study. Materials and Methods: Cone beam computed tomography volumetric scan was used as a control group, as it has been considered as a gold standard in terms of accuracy. For comparison, scan data were obtained from three different scanners, namely Carestream facial scanner, Medit intraoral scanner for facial scan, and MetiSmile face scanner. The standard tessellation language files thus obtained were compared for accuracy in Geomagic X software by superimposition technique and were evaluated for their accuracy using various reference points on the face. Statistical Analysis Used: Normality was confirmed using the Shapiro–Wilk test. One-way analysis of variance for comparison among groups and Tukey test for pairwise comparison was used using SPSS software (IBM SPSS version 29 USA). Results: The study concluded that MetiSmile was the best facial scanner among the three groups with a mean discrepancy of (0.35 ± 0.33) mm and P = 0.001, indicating significant difference between the scanners. Conclusion: Each scanner evaluated demonstrated acceptable performance, with notable variations attributable to their distinct scanning methodologies. Among these, the MetiSmile scanner emerged as the most accurate, delivering the most favorable results in terms of accuracy.